The Politics of American Values in Barack Obama’s Life Narratives: A Rhetorical Analysis of National Ethos - Bhusal, Mahendra (Pursuits: A Journal of English Studies, 2024)
Barack Obama weaves a sequence of his personal story rhetorically to evoke American national ethos, with a special emphasis on American values making them an integral part of his memoirs, especially his The Audacity of Hope (2006). This paper interrogates why he narrates the story of typical American values in his political memoir in general and ascertain them in a dedicated section titled ‘Values’ in particular to explore the implicit dimensions of his storytelling. Form the theoretical parameters of Walter R Fisher’s ‘narrative paradigm’ this paper contends that, by way of recognizing (assimilating or internalizing) typical American values, Obama prepares a ground for Fisher’s ‘narrative rationality’ to identify himself with American character and American people, and thereby evokes American national ethos to assume a statesmanship.